Reliability and Performance Analysis of Standby Generator Systems for Enhancing Electrical Resilience at Sentani International Airport - Arta, I Wayan Yogi; Palpialy, Jemi Victor (Jurnal Ragam Pengabdian, 2026)
The reliability of a standby power system is essential for maintaining airport operations during disruptions to the primary electricity supply. Generator sets (gensets) serve as emergency power sources for critical facilities, including the Airfield Lighting System (AFL), Air Traffic Control (ATC), communication systems, and air navigation equipment. This study analyzes the reliability of the standby generator system at Sentani International Airport, evaluates its maintenance management, identifies factors affecting reliability, and examines its contribution to airport power resilience. A qualitative case study approach was employed using in-depth interviews, direct observations of two 1000 kVA generator units and supporting systems, and document analysis of maintenance records and operational procedures. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while credibility was ensured through triangulation and member checking. The findings show that the standby generator system provides reliable backup power through redundant generator units, an Uninterruptible Power Supply (UPS), and structured preventive maintenance. Nevertheless, system reliability is constrained by a semi-automatic Automatic Transfer Switch (ATS) requiring 30–40 seconds for power transfer, limited digital fuel monitoring, utility voltage fluctuations, and logistical constraints. The study proposes an integrated framework combining technical, maintenance, power transfer, and organizational aspects to strengthen airport electrical system resilience.